Omnidirectional surveillance system using thermal camera - Wong, W.K.; Tan, P.N.; Loo, C.K.; Lim, W.S. (2010)
Thermography, or thermal visualization is a type of infrared visualization. Thermographic cameras are used in many heavy factories like metal recycling factories, wafer production factories and etc for monitoring the temperature conditions of the machines. Besides, thermographic camera can be used to detect trespassers in environment with poor lighting condition, whereby, the conventional digital cameras are less applicable in. This paper proposed an efficient omnidirectional surveillance system using thermal camera. In this surveillance system, the omnidirectional scenes in a machine room, production plant, pump house, laboratory, etc within a factory site are first captured using a thermal camera attached to a custom made hyperbolic IR (infrared radiation) reflected mirror. The captured scenes with some machines to be monitored are then fed into a laptop computer for image processing and alarm purposes. Log-polar mapping is proposed to map the captured omnidirectional thermal image into panoramic image, hence providing the observer or image processing tools a complete wide angle of view. Two simple and fast detection algorithms are embedded into the thermal imaging surveillance system. This surveillance system is not only used for monitoring the functioning condition of different machines/items in a factory site, but can also use for detecting the trespassers in a poor lighting condition. The observed significances of this new proposed omnidirectional thermal imaging system include: it can cover a wide angle of view (360Â° omnidirectional), using minimum hardware, low cost and the output thermal images are with higher data compression. Experimental results show that the proposed surveillance system achieves high accuracy in monitoring machines conditions and detecting trespassers.